Antibiotics in Bone Cements Used for Prosthesis Fixation: An Efficient Way to Prevent Staphylococcus aureus and Staphylococcus epidermidis Prosthetic Joint Infection - Cara, Andréa; Ballet, Mathilde; Hemery, Claire; Ferry, Tristan; Laurent, Frédéric; Josse, Jérôme (Frontiers in Medicine, 2021)
Prosthetic joint infections are one of the most frequent reasons for arthroplasty revision. These infections are mostly associated to the formation of biofilm, notably by staphylococci such as S. aureus and S. epidermidis.. To minimize the rates of PJIs following primary or revision total joint arthroplasty, antibiotic-loaded bone cements (ALBC) can be used for prosthesis fixation. However, its use is still debated. Indeed, various studies reported opposite results.. In this context, we aimed to compare the prophylactic anti-biofilm activity of ALBCs loaded with 2 antibiotics with ALBC loaded with only one antibiotic. We compared commercial ready-to-use cements containing gentamicin alone, gentamicin plus vancomycin and gentamicin plus clindamycin to plain cement (no antibiotic), investigating staphylococcal biofilm formation for ten strains of S. aureus and S. epidermidis with specific resistance to gentamicin, vancomycin or clindamycin. Firstly, we performed disk diffusion assays with the elution solutions. We reported that only the cement containing gentamicin and clindamycin was able to inhibit bacterial growth at Day 9 whereas cements with gentamicin only or gentamicin and vancomycin lost their antibacterial activity at Day 3. Then, we observed that all the tested ALBCs can inhibit biofilm formation by methicillin-susceptible staphylococci without other antibiotic resistance ability. Similar results were observed when we tested vancomycin-resistant or clindamycin resistant staphylococci, with some strain-dependent significant increase of efficacy for the two-antibiotic ALBCs when compared to gentamicin-loaded cement. However, adding vancomycin or clindamycin to gentamicin allows a better inhibition of biofilm formation when gentamicin resistant strains were used. Our in vitro results suggest that using commercially available bone cements loaded with gentamicin plus vancomycin or clindamycin for prosthesis fixation can help preventing staphylococcal PJIs following primary arthroplasties, non-septic revisions or septic revisions, especially to prevent PJIs caused by gentamicin-resistant staphylococci.